Challenges of interprofessional geriatric practice in home care settings: an integrative review. Issue 2 (3rd April 2023) - Song, Youngkwan; Jung, Min Young; Park, Sungwon; Hasnain, Memoona; Gruss, Valerie
ABSTRACT: This integrative review identified challenges for interprofessional home care and provided recommendations for improving geriatric home care. A search of six databases identified 982 articles; 11 of them met the review's eligibility criteria and were included in the review. Quality appraisal of the included studies was performed using two tools (Critical Appraisal Skills Program for Qualitative Research and Mixed Methods Appraisal Tool), and their overall methodological quality was found to be satisfactory. After applying D'Amour et al.'s framework, four "challenge" themes emerged: (1) lack of sharing, (2) lack of partnership, (3) limited resources and interdependency, and (4) power issues. Recommendations included providing practical multidisciplinary training guided by a standardized model, establishing streamlined communication protocols and a communication platform reflecting the actual needs of users by involving them in its design, and asking interprofessional team members to commit to home care planning and to cultivate a collaborative culture and organizational support.